Dynamics Encounter of Tradition and Religion in the Wedding Parade (Baarak Bako) in Solok City West Sumatra - Azwar, Zainal; Majid, Hamidun; Firdaus, Firdaus; Zulfan, Zulfan; Arlis, Arlis (Fakultas Syariah UINSI Samarinda, 2023)
Islamic Sharia stipulates that marriages must be announced to the public. One method of the announcement is through walīmat al-‘urs, translated differently in different Muslim communities. In the city of Solok, West Sumatra, one of the forms of walīmat al-‘urs is the baarak bako tradition (a wedding parade around the village). Baarak bako's implementation frequently clashes with obligatory prayer times in Islam, causing many participants to leave the prayer. This research aims to examine the background of the baarak bako tradition, the reasons for deciding the time to perform baarak bako, and the effects of baarak bako on prayer services. Using a qualitative method, this article revealed that the origin of baarak bako was the desire of the bako (father's female family) to show their presence by enlivening anak pisang's (the children of a brother) wedding. According to the custom, the best time to announce a marriage is in the afternoon because people are already at home and have finished their activities outside the home; the implementation of baarak bako resulted in some participants failing to perform the obligatory prayers. The neglected prayers are carried out in jama' (merging two prayers). Others, on the other hand, leave the prayer without jama'. The people of Solok City are very rigorous about following customary rules. When religious law and customary law rules conflict, some people prefer customary rules over religious rules and vice versa. These findings show the dynamic relationship between religion and customs in the Minangkabau ethnic group, West Sumatra. These two norms can coexist and adapt to each other in practice. Keywords: Islamic law, prayers, marriage, tradition, baarak bako.